Environmental DNA sequencing reveals the regional difference in diversity and community assembly mechanisms of eukaryotic plankton in coastal waters - Yan, Zhen-Guang; Zhu, Xue-Ming; Zhang, Shou-Wen; Jiang, Hua; Wang, Shu-Ping; Wei, Chao; Wang, Jie; Shao, Yun; Liu, Chen; Wang, Hui (Frontiers in Microbiology, 2023)
The diversity and community assembly mechanisms of eukaryotic plankton in coastal waters is so far not clear. In this study, we selected the coastal waters of Guangdong-Hong Kong-Macao Greater Bay Area, which is a highly developed region, as the research area. By use of high-throughput sequencing technologies, the diversity and community assembly mechanisms of eukaryotic marine plankton were studied in which a total of 7295 OTUs were obtained, and 2307 species were annotated by doing environmental DNA survey of 17 sites consist of surface and bottom layer, respectively. Ultimately, the analysis reveals that the species abundance of bottom layer is, by and large, higher than that in the surface. In the bottom, Arthropoda is the first largest group, accounting for more than 20% while Arthropoda and Bacillariophyta are dominant groups in surface waters, accounting for more than 40%. It is significant of the variance in alpha-diversity between sampling sites, and the difference of alpha-diversity between bottom sites is greater than that of surface sites. The analysis suggests that the environmental factors that have significant influence on alpha-diversity are total alkalinity and offshore distance for surface sites, and water depth and turbidity for bottom sites. Likewise, the plankton communities obey the typical distance-decay pattern. Analysis about community assembly mechanisms reveals that, overall, dispersal limitation is the major pattern of community formation in this study, which accounts for more than 83% of the community formation processes, suggesting that stochastic processes are the crucial assembly mechanism of the eukaryotic plankton community in the study area.